Enrichment Pupuk Organik Asal Kotoran Ternak di CV Gumukmas Multi Farm Jember - Dwi Erwin Kusbianto; Listya Purnamasari; Himmatul Khasanah (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
CV Gumukmas Multi Farm as a service partner is one of the entrepreneurs in the sociopreneur-based livestock sector who collaborates with smallholder farmers as partners. The problem faced by partners is the high population of sheep that are kept so that they produce abundant livestock manure but are not used optimally so that they pollute the environment. The solution is structured training and demonstration in the manufacture of nutrient-rich organic fertilizer. Success in the management of manure waste is indicated by the results of compost that resemble soil and do not smell. This service program has improved the skills of farmers in managing livestock manure waste into processed organic fertilizers that can be used in agricultural land/forage for animal feed and improving the environmental conditions of the cages to be cleaner and healthier.